Functional Assays of Protein C: Comparison of Two Snake-Venom Assays with Two Thrombin Assays - Franchi, F; Tripodi, A; Valsecchi, C; Mannucci, P M (Thrombosis and Haemostasis, 1988)
Protein C (PC) activities measured by two thrombin-based assays have been compared with those obtained by two assays based on snake venom activation of plasma PC followed by measurement of both the amidolytic and anticoagulant activities of activated PC. This study indicates that snake venom assays gave results similar to those of the thrombin assays in 20 healthy subjects, in 16 patients with DIC and in 15 patients with congenital PC deficiency. There was, however, some degree of misclassification of normals and congenitally-deficient patients, with only the clotting snake venom assay resulting in no misclassifications. In 15 patients stabilized on warfarin treatment and in 17 with liver disease, the clotting snake venom assay gave significantly lower values than the other assays, so that it might prove to be more sensitive than the other assays to these defects.
Keywords: Protein C; Snake venoms; Congenital thrombophilia